Proceedings of the 45th IEEE Conference on Decision and Control 2006
DOI: 10.1109/cdc.2006.377555
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for 3D UAV Path Generation and Tracking

Abstract: In this paper we consider the problem of 3D path generation and tracking for unmanned air vehicles (UAVs). The proposed path generation algorithm allows us to find a path satisfying arbitrary initial and final conditions, specified in terms of position and velocity. Our method assumes that most of aircraft structural and dynamic limitations can be translated in a turn radius constraint; therefore, the generated paths satisfy a constraint on the minimum admissible turning radius. The proposed algorithm for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…In each case, the aircraft initial altitude and wind conditions were allowed to vary, while the initial and final Fig. 8 Using the speed polar diagram while gliding in winds (Image obtained from [12] aircraft headings and positions were kept constant. A Monte Carlo simulation using a larger input set will be performed at a later date.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each case, the aircraft initial altitude and wind conditions were allowed to vary, while the initial and final Fig. 8 Using the speed polar diagram while gliding in winds (Image obtained from [12] aircraft headings and positions were kept constant. A Monte Carlo simulation using a larger input set will be performed at a later date.…”
Section: Resultsmentioning
confidence: 99%
“…Once the radii are determined, the optimal 2D path is obtained with a geometrical construction adapted from [12]. Initially, two circles with radii R 0 are drawn containing the starting point P 0 and a vector pointing along the aircraft's initial heading ψ 0 (Figure 3a).…”
Section: Path Planningmentioning
confidence: 99%
“…We used for the path generation in the Alignment phase the algorithm, developed by CIRA and University "Federico II" of Naples, described in detail 12,14 . This Alignment algorithm is based on the Dubins method 13 to generate a planar trajectory satisfying initial and terminal conditions, specified in terms of position and heading…”
Section: Fully Adaptive Autonomous Landing Algorithmmentioning
confidence: 99%
“…Once the waypoints and path elements are planned, a suitable path tracking algorithm must be found. An example of a stable non-linear tracking controller is presented by Ambrosino et al (2006). As an elegant way to determine a suitable flight path and a vehicle guidance law at the same time, Lawrence et al (2008) proposed a vector field technique that is shown to have Lyapunov stability properties.…”
Section: Localisation and Navigationmentioning
confidence: 99%